2013
DOI: 10.26719/2013.19.3.255
|View full text |Cite
|
Sign up to set email alerts
|

Screening for BRCA1 large genomic rearrangements in female Egyptian hereditary breast cancer patients

Abstract: Approximately 5%-10% of all breast cancers are inherited as the result of germline mutations in the BRCA1 gene. Large genomic rearrangements (LGRs) in BRCA1 have not been well-researched in the Egyptian population. Using multiplex ligation-dependent probe amplification, we showed BRCA1 rearrangements in 4/22 cases (18.2%) of familial breast cancer. No influence of having multiple breast cancer cases within the family was observed in patients diagnosed at < or ≥ 45 years and having BRCA1-positive LGRs. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Additional studies on BRCA genes have expanded to identifying the population-based mutation frequency and screening/genetic testing in the Democratic Republic of the Congo ( 80 ), Morocco ( 81 ), Tunisia ( 82 , 83 ), Algeria ( 84 , 85 ), familial studies in Morocco ( 86 , 87 ), and large genomic rearrangement in Egypt ( 88 , 89 ). Of these, the contribution of BRCA mutations to male breast cancer was reported only in the Moroccan study by Guaoua et al ( 86 ).…”
Section: Resultsmentioning
confidence: 99%
“…Additional studies on BRCA genes have expanded to identifying the population-based mutation frequency and screening/genetic testing in the Democratic Republic of the Congo ( 80 ), Morocco ( 81 ), Tunisia ( 82 , 83 ), Algeria ( 84 , 85 ), familial studies in Morocco ( 86 , 87 ), and large genomic rearrangement in Egypt ( 88 , 89 ). Of these, the contribution of BRCA mutations to male breast cancer was reported only in the Moroccan study by Guaoua et al ( 86 ).…”
Section: Resultsmentioning
confidence: 99%
“…Genetic testing of BC and OC has gained research momentum recently in the Middle East (Amemiya et al, ; Hagag, Shwaireb, Coffa, & El Wakil, ). In their review of BRCA1 mutations in the Middle East and North Africa (MENA) region, Laraqui et al concluded that the high prevalence of BC and the presence of frequent mutations of the BRCA1 gene emphasizes the need to improve screening programs and individual counseling (Laraqui et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Although pockets in the North and South of the continent have initiated genetic testing for BRCA mutations, genetic and genomic testing remains a philosophical discussion for most of the African continent. 75,76 The testing of genomics and transcriptomics largely lies beyond the scope of most laboratory facilities in developing countries.…”
Section: Application Of Breast Cancer Genomics In Developing Countriesmentioning
confidence: 99%